ANALISIS KEMAMPUAN SISWA MENYELESAIKAN MASALAH MATEMATIS PADA KONSEP BARISAN GEOMETRI - Wangsa, Arma; Mashuri, Sufri; Marniati, Marniati; Marillah, Dima; Rosti, Rosti (Almeera Education, 2025)
Indonesian students' performance still tends to be low in solving mathematical problems. In order to explore this issue, further studies are needed to determine the ability of students to solve mathematical problems in various mathematical materials. Therefore, this study aims to describe students' mathematical problem solving ability on geometric sequence material. Descriptive qualitative method was used to describe three research subjects (students of SMAN 6 Bombana) who each represented high, medium, and low ability levels. Tests and interviews were given to collect data which were then analyzed to find out how students' work and errors in solving mathematical problems. The results showed that based on Polya's problem solving indicators, subjects with high and medium ability could solve the problem well, although subjects with medium ability needed two attempts (changing the solution plan) to get the correct answer. Meanwhile, subjects in the low category could not solve the mathematical problems presented in three attempts. In addition, two student errors were found in the solution process, namely: 1) incorrectly using the concept; and 2) incorrectly determining the ratio of the sequence. This study also found a positive participation of adversity quotient as a good mentality for students in solving mathematical problems.